Drug Intensification in Future Postoperative Radiotherapy Practice in Biochemically-Relapsing Prostate Cancer Patients - Cailleteau, Axel; Sargos, Paul; Saad, Fred; Latorzeff, Igor; Supiot, Stéphane (Frontiers in Oncology, 2021)
Although salvage prostate bed radiotherapy is highly effective in biochemically-relapsing prostate cancer patients following prostatectomy, relapses are frequent and improvements are needed. Randomized phase 3 trials have shown the benefit of adding androgen-depriving therapy to irradiation, but not all patients benefit from this combination. Preclinical studies have shown that novel agents targeting the androgen receptor, DNA repair, PI3K/AKT/mTOR pathways, or the hypoxic microenvironment may help increase the response to prostate bed irradiation while minimizing potential side effects. This perspective review focuses on the most relevant molecules that may have an impact when combined with salvage radiotherapy, and underlines the strategies that need to be developed to increase the efficacy of salvage post-prostatectomy radiotherapy in prostate cancer patients.